Cloning and expression of cDNAs for two distinct murine tumor necrosis factor receptors demonstrate one receptor is species specific. - Lewis, M (1991)
Complementary DNA clones encoding two distinct tumor necrosis factor receptors were isolated from a mouse macrophage cDNA library. The cDNA for murine tumor necrosis factor receptor type 1 (mTNF-R1) predicts a mature polypeptide of 425 amino acids that is 64% identical to its human counterpart, whereas the cDNA of murine tumor necrosis factor receptor type 2 (mTNF-R2) predicts a mature protein of 452 amino acids that is 62% identical to human tumor necrosis factor receptor type 2. The two murine tumor necrosis factor receptors have limited sequence homology (approximately 20% identity) in their extracellular regions but no apparent similarity in their cytoplasmic portions. Northern (RNA) analysis indicates a single 2.6-kilobase (kb) transcript for mTNF-R1; a 3.6-kb and a more predominant 4.5-kb transcript are observed for mTNF-R2. A human cell line transfected with either mTNF-R1 or mTNF-R2 expression vectors specifically bound 125I-labeled recombinant murine tumor necrosis factor alpha (TNF-alpha). Although mTNF-R1 had a similar affinity for both recombinant murine TNF-alpha and human TNF-alpha, mTNF-R2 showed strong specificity for recombinant murine TNF-alpha. This result suggests that the various activities of human tumor necrosis factor alpha reported in mice or in murine cell lines are probably mediated by mTNF-R1.